2015
DOI: 10.1096/fj.15-275487
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin and resolvin biosynthesis is dependent on 5‐lipoxygenase activating protein

Abstract: Resolution of acute inflammation is an active process coordinated by proresolving lipid mediators (SPMs) such as lipoxins (LXs) and resolvins (Rvs), which are formed by the concerted action of 2 lipoxygenases (LOs). Because the exact molecular mechanisms of SPM biosynthesis are not completely understood, we aimed to investigate LX and D-type Rv formation in human leukocytes and HEK293T cells overexpressing leukotriene (LT) pathway enzymes. Activity assays in precursor (15-hydroxyeicosatetraenoic acids, 17-HDoH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 45 publications
(95 reference statements)
3
48
0
Order By: Relevance
“…The literature on 5-LO in M1 and M2 Mfs is controversial. Higher 5-LO and FLAP protein expression has been reported for M1 (23), whereas other reports showed that ALOX5 mRNA was higher in M2 compared with M1 (5, 24). CLP, the other 5-LO accessory protein that also binds to F-actin, was slightly higher in M-CSF Mfs, whereas LTA 4 hydrolase was equally expressed in both cell types.…”
Section: Expression Of Eicosanoid-forming Enzymes Is Different In Gm-mentioning
confidence: 81%
“…The literature on 5-LO in M1 and M2 Mfs is controversial. Higher 5-LO and FLAP protein expression has been reported for M1 (23), whereas other reports showed that ALOX5 mRNA was higher in M2 compared with M1 (5, 24). CLP, the other 5-LO accessory protein that also binds to F-actin, was slightly higher in M-CSF Mfs, whereas LTA 4 hydrolase was equally expressed in both cell types.…”
Section: Expression Of Eicosanoid-forming Enzymes Is Different In Gm-mentioning
confidence: 81%
“…LTC4, LTD4 and LTE4 are known collectively as the cysteinyl leukotrienes and are reported to have a role in inflammatory cell recruitment, smooth muscle contraction, vessel dilation and permeability [53] (Figure 2). 5-LO is also involved in the synthesis of another type of AA-derived metabolite called Lipoxins, such as LXA4 and LXB4 which have anti-inflammatory and pro-resolving properties [54,55]. …”
Section: 5-lipoxygenase Pathway In Cancermentioning
confidence: 99%
“…PBMC isolation was performed as previously described [26]. Subsequently, T and B cell selection were carried out using T Cell Enrichment kit as well as Dynabeads Untouched Human B Cell kit according to manufacturer´s protocol.…”
Section: Methodsmentioning
confidence: 99%